Świat stworzony w literaturze wczesnochrześcijańskiej (Sekcja Patrystyczna, Tarnów, 17-20.09.2023) - Pakowski, Grzegorz (Vox Patrum, 2024)
Report from the meeting of the Polish Patristic Section on the theme "The Created World in Early Christian Literature" that was held in Tarnów on 17-20.09.2023.